2020
DOI: 10.1007/s11244-020-01304-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Promoting Effects of Te and Nb in the Activity and Selectivity of M1 MoV-Oxides for Ethane Oxidative Dehydrogenation

Abstract: The pathways of ethane oxidative dehydrogenation and total combustion have been elucidated for M1 phase type Mo-V oxide catalysts with different metal composition. The ethane oxidation mechanism is not affected by the presence of Te or Nb. Conversely, the selectivity is strongly affected by stoichiometry of M1 catalysts. This is attributed to the facile oxidation of ethene to CO x upon formation of unselective VO x species in the absence of Te and Nb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…4), where the C–H bond is activated by a V 5+ site, α-hydrogen abstraction of allylic species by a Te 4+ site, and an N-insertion by a Mo 6+ site. 67 Moreover, it was found that the AN yield could be improved with a higher extent of the M1 phase (Fig. 5).…”
Section: Synthesis Of Nitrilesmentioning
confidence: 87%
See 1 more Smart Citation
“…4), where the C–H bond is activated by a V 5+ site, α-hydrogen abstraction of allylic species by a Te 4+ site, and an N-insertion by a Mo 6+ site. 67 Moreover, it was found that the AN yield could be improved with a higher extent of the M1 phase (Fig. 5).…”
Section: Synthesis Of Nitrilesmentioning
confidence: 87%
“…Reproduced with permission. 67 Copyright 2020, Springer Nature. 7), in which MovO sites are perturbed by Bi.…”
Section: Perspectivementioning
confidence: 99%
“…The particular difficulty is to reach a sufficient yield of valuable products such as olefins or unsaturated oxygenates, that is, to achieve high selectivity of these products at high conversion, while avoiding total oxidation to CO 2 . Numerous studies in the literature and in our own laboratories have investigated these reactions. However, very diverse reaction conditions have been applied, as shown by the literature survey presented in Table S1. This makes a direct comparison of the catalysts impossible and potentially systematic trends not apparent.…”
Section: Alkane Selective Oxidationmentioning
confidence: 99%
“…5,13 The oxidative dehydrogenation (ODH) of ethane (C 2 ) is a prospective reaction route for the on-demand production of ethylene using similar catalysts. 14,15 One of the main challenges in understanding the underlying catalytic principles is the dynamic behaviour and selfadapting nature of the catalysts under reaction conditions. [16][17][18][19] In literature, this phenomenon is described as 'flexible surfaces', where the chemical potential of the gas phase affects the surface state and changes the surface composition of the bulk catalyst.…”
Section: Introductionmentioning
confidence: 99%